PRIMARY RENAL LYMPHOMA IN TWO CATS: CASE REPORT - Ambrosini, Francielli; Garcia, Melissa; Silva, Victória Gariba e; Rossa, Ana Paula; Alves, Thais Landarin; Sousa, Renato Silva de; Albernaz, Vinicius Gonzalez Peres; Sousa, Marlos Gonçalves; Stedile, Simone Tostes de Oliveira (Archives of Veterinary Science, 2021)
Lymphoma is a hematopoietic neoplasia which occurs due to the proliferation of malignant lymphocytes. It can be present in different forms, including alimentary, mediastinal, multicentric and extranodal. In both cases described in this report, signs consistent with chronic kidney disease were present. An ultrasound-guided fine-needle aspiration was performed and suggested a lymphocyte neoplastic process. Both cats received prednisolone and life support treatment, with mild improvement. One cat was euthanatized and the other died spontaneously, five and seven days after onset of treatment, respectively. The kidneys were enlarged, whitish, irregular, with a firm mass in the cortex. Histopathology confirmed that the lymphoma was restricted to the kidneys.